2004
DOI: 10.1023/b:aibe.0000030249.11679.d0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviors and Risks Among Bisexually- and Gay-Identified Young Latino Men

Abstract: This research compares patterns of sexual behavior and sexual risk of bisexually- and gay-identified Latino young men who have sex with men (YMSM). Four hundred forty-one Latino YMSM were surveyed at community venues in New York City. Twenty-two percent of the sample identified as bisexual, and 78% identified as gay. Bisexually-identified men were more likely to report having had multiple male sex partners in the last 3 months and less likely to report being exclusively involved with a main male partner. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 29 publications
4
61
0
Order By: Relevance
“…Although youth who identify as bisexual have received less attention in the literature than gay-identified individuals, these findings suggest that they may be similar to heterosexual YMSM in some respects. Further, our findings are consistent with other research studies that have found bisexuals to be at heightened risk for sexual risk behavior and adverse outcomes, including participation in sex work (Agronick et al, 2004;Logan & Leukefeld, 2000; National Institute on Drug Abuse, 2000). We expect that factors other than participation in sex work are involved in lower rates of resilience in these two important subpopulations, and future research on these groups is warranted.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although youth who identify as bisexual have received less attention in the literature than gay-identified individuals, these findings suggest that they may be similar to heterosexual YMSM in some respects. Further, our findings are consistent with other research studies that have found bisexuals to be at heightened risk for sexual risk behavior and adverse outcomes, including participation in sex work (Agronick et al, 2004;Logan & Leukefeld, 2000; National Institute on Drug Abuse, 2000). We expect that factors other than participation in sex work are involved in lower rates of resilience in these two important subpopulations, and future research on these groups is warranted.…”
Section: Discussionsupporting
confidence: 91%
“…& Stueve, 2002;Thiede et al, 2003;Valleroy et al, 2000). Among YMSM, those who do not identify as gay or homosexual and those who consider themselves transgender appear to be at greatest jeopardy for adverse outcomes (Agronick et al, 2004;Cooper, 1999;Hughes & Eliason, 2002). Overall, YMSM are a hidden and hard-to-reach population, mainly because of stigma and often because of their involvement in illegal activities (MacKellar, Valleroy, Karon, Lemp, & Janssen, 1996;Muhib et al, 2001).…”
mentioning
confidence: 99%
“…Given the rapid growth of the Latino population in the United States (U.S. Census Bureau, 2011;Ennis et al, 2011) the marginalization experienced by Latina lesbians, and the pervasive homophobic and heterosexist climate within Latino communities (Agronick et al, 2004;Green, 1994;Ryan et al, 2009;Encarnacioń, 2011), this study provides critical insights for best practices in higher education.…”
Section: Problem Statementmentioning
confidence: 97%
“…Additionally, a collective Latino value and constraint concerning the makeup of the family unit (that it consists of one man, one woman, and children), coupled with religious views that homosexuality is wrong, situates Latina lesbians as a marginalized and oppressed group (Agronick et al, 2004;Sandfort, Melendez, & Diaz, 2013;Chaturvedi, 2014).…”
Section: Background Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation